New Straits Times, 08 January 2007 - Zaidi Isham Ismail (The New Straits Times Press (M) Bhd, 2007)
Malays must be cemerlang, gemilang and terbilang for the country to be a global economic player and lead the Islamic world as generators of technology and nor just as users of technology.